Operationalising transboundary cooperation through game theory: An energy water food nexus approach for the Middle East and North Africa - Sarah Namany (17268922) (2023)
The Middle East and North African (MENA) countries are subject to natural and anthropogenic stressors that inhibit environmental conservation, economic development and social stability, creating a potential for socio-economic disparities between them. The current parochialistic approach adopted by majority of the MENA countries continues to foster competition, despite the complementary relationships that can potentially arise between their resource systems. Consequently, food security is one area which is vastly suffering at unprecedented scales threatening the prosperity in the MENA region. On the other hand, the MENA countries share similar socio-economic and geo-political characteristics, and therein lies an opportunity to create a novel strategic ecosystem for enhancing cooperation between them to achieve greater resilience in regional food security. In this paper, the tools used to model competition and the enabling mechanisms for cooperative approaches were reviewed, including applications of non-cooperative and cooperative game theory in EWF nexus systems. A real-life example of the usefulness of game theoretic models is illustrated through a transboundary EWF nexus-based cooperative framework which links the available resources and assets in the MENA region and offers a fertile field to enhance food security and greater socio-economic and environmental resilience in the region. Other Information Published in: Futures License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.futures.2023.103198